The Axiomatic Foundation of Logit - Yves Breitmoser (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
Multinomial logit is the canonical model of discrete choice but widely criticized for requiring functional form assumptions as foundation. The present paper shows that logit is behaviorally founded without such assumptions. Logitś functional form obtains if relative choice probabilities are independent of irrelevant alternatives and invariant to utility translation, to relabeling options (presentation independence), and to changing utilities of third options (context independence). Reviewing behavioral evidence, presentation and context independence seem to be violated in typical experiments, though not IIA and translation invariance. Relaxing context independence yields contextual logit (Wilcox, 2011), relaxing presentation independence allows to capture f̈ocalityöf options.
Keywords: D03; C13; 330; stochastic choice; logit; axiomatic foundation; behavioral evidence; utility estimation